2021
DOI: 10.3389/fimmu.2020.628923
|View full text |Cite
|
Sign up to set email alerts
|

Human IgA-Expressing Bone Marrow Plasma Cells Characteristically Upregulate Programmed Cell Death Protein-1 Upon B Cell Receptor Stimulation

Abstract: The functions of bone marrow plasma cells (BMPC) beyond antibody production are not fully elucidated and distinct subsets of BMPC suggest potential different functions. Phenotypic differences were identified for human BMPC depending on CD19 expression. Since CD19 is a co-stimulatory molecule of the B-cell-receptor (BCR), and IgA+ and IgM+ BMPC express the BCR on their surface, we here studied whether CD19 expression affects cellular responses, such as BCR signaling and the expression of checkpoint molecules. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…This is consistent with both childhood vaccine specificities being enriched in the CD19‐negative bone marrow ASC population, 9,17,18 and with CD19‐negative ASCs being present in bone marrow aspiration samples from B‐cell cancer patients post anti‐CD19 CAR‐T‐cell infusion who also retained certain vaccine/pathogen reactivities 19 . Somewhat confusingly, however, vaccine‐specific Ab levels were also largely retained in atacicept‐treated patients, 10 indicating either those vaccine‐specific ASCs reside in a CD19‐negative, APRIL‐independent compartment or there is a broad distribution of specificities among bone marrow ASC compartments, which is suggested by other studies 20,21 . The complete characterisation of the different subpopulations of B cells and ASCs in both health and autoimmune disease will greatly assist in improved targeting of pathogenic, autoreactive B cells and ASCs.…”
Section: Figuresupporting
confidence: 65%
See 1 more Smart Citation
“…This is consistent with both childhood vaccine specificities being enriched in the CD19‐negative bone marrow ASC population, 9,17,18 and with CD19‐negative ASCs being present in bone marrow aspiration samples from B‐cell cancer patients post anti‐CD19 CAR‐T‐cell infusion who also retained certain vaccine/pathogen reactivities 19 . Somewhat confusingly, however, vaccine‐specific Ab levels were also largely retained in atacicept‐treated patients, 10 indicating either those vaccine‐specific ASCs reside in a CD19‐negative, APRIL‐independent compartment or there is a broad distribution of specificities among bone marrow ASC compartments, which is suggested by other studies 20,21 . The complete characterisation of the different subpopulations of B cells and ASCs in both health and autoimmune disease will greatly assist in improved targeting of pathogenic, autoreactive B cells and ASCs.…”
Section: Figuresupporting
confidence: 65%
“…19 Somewhat confusingly, however, vaccine-specific Ab levels were also largely retained in atacicept-treated patients, 10 indicating either those vaccine-specific ASCs reside in a CD19-negative, APRIL-independent compartment or there is a broad distribution of specificities among bone marrow ASC compartments, which is suggested by other studies. 20,21 The complete characterisation of the different subpopulations of B cells and ASCs in both health and autoimmune disease will greatly assist in improved targeting of pathogenic, autoreactive B cells and ASCs.…”
mentioning
confidence: 99%
“…In B cells, CD81 is part of the BCR complex that includes CD21 and CD19 and reduces the threshold for B cell activation. It was believed that ASCs no longer had a functional BCR, but this idea has to be reconsidered in light with reports showing that IgM and IgA ASCs still have a functional surface BCR (4,57,58). Thus, CD81 may play a role in the activation of ASCs, being therefore also more than just a marker for their identification.…”
Section: Discussionmentioning
confidence: 99%
“…Different subsets of ASCs have been described in mouse and human. For instance, a subset of CD19human bone marrow ASCs expressing high levels of programmed cell death protein-1 was recently reported (4). Collectively, ASCs form a heterogeneous population containing several subpopulations with different functions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in mice have shown that PCs can also regulate immunity through production of anti-inflammatory cytokines such as interleukin (IL)-10 and IL-35. 1 , 2 , 3 , 4 Distinct PC subsets with protective and pathogenic functions have been identified by the expression of certain surface markers in both mouse and humans, 1 , 3 , 5 , 6 providing possible selective depletion approaches of the pathogenic cells in various diseases. Nevertheless, this strategy is limited as those surface markers are also expressed by other immune cell lineages.…”
Section: Introductionmentioning
confidence: 99%